Entrenamiento en técnicas de mediación para el manejo de los conflictos escolares dirigido a los docentes de la escuela de educación básica Rosa Grimaneza Ortega, Loja 2014-2015 - Asanza Apolo, Ricardo David (2016)
This research is aimed at training in mediation techniques for handling school´s conflicts by teachers of basic education at Rosa Grimaneza Ortega School in Loja during the 2014-2015 academic period, which was based on a descriptive and explanatory study of quasi experimental and cross-sectional where the methods used were: scientific, descriptive, inductive, deductive, understanding, diagnosis, and statistical modeling. The instrument selected was Modes of Conflict form Thomas-Kilmann that was designed to evaluate the behavior of teachers facing conflict situations. The population of the research was conducted at approximately 7 educators taking into consideration that the conflicts that occur in the institution are challenges for society but which directly affects the teachers. Amongst the most significant results that could be obtained is highlighted in relation to the diagnosis through pre-test where teachers presented evasive behavior to conflict situations at a high level. To this, it was developed and implemented a series of workshop´s intervention for trying to reduce existing conflicts with teachers So, it can be concluded that teachers consolidated best ways of action against conflicting situations reaching an assertive, cooperative and collaborative culture, confronting and managing conflict situations constructively. Additionally, by linear correlation from Pearson coefficient in evasion mode it was obtained a value of 0.44 belonging to a moderate positive correlation, it meant that the intervention influent in this area. Finally, the results obtained on the investigated population were socialized with the school principal in order to encourage the authorities of the institution to be opened for future projects that as a result increase and strength the school life necessary to promote the good environment in education.